Internet, smart devices and family, case study, UTPL Madrid students - Fernández-Álvarez, Nicolás; Yaguana-Romero, Hernán; Arrobo-Agila, Juan Pablo (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The purpose of this research is to find out about the use of Internet and mobile telephony within the reality of university students. For its analysis a mixed methodology of exploratory character was applied, the techniques used, on the one hand, the qualitative one was applied by means of semi-structured interviews, the quantitative technique, on the other hand a survey was applied to 100% of the students of the university center, relatives and one or the other of the university authorities. The most frequent activities, when introducing the Internet and the cell phone are: family and work communication, entertainment and study.